Integrating a Service-Learning Approach into Arabic Language Instruction, Along with Fun-Learning and a Participatory Appreciation System, to Enhance Students’ Motivation at the Rumah Quran Raudhatul Quran. - dwimeutiahasni_16 Dwi Meutia Hasni; Dina Marni; Rozaanah; Aisyah Luthfiah Zahra (As-sunnah: Jurnal Pengabdian Masyarakat, 2026)
Rumah Qur’an (RQ) Raudhatul Hufadz, a non-formal Qur’anic learning center in Sei Mencirim Village, Deli Serdang Regency, faced two intertwined problems: children showed strong enthusiasm for learning yet had no access to structured Arabic instruction, and the existing tahfidz (Qur’an memorization) program suffered from flagging motivation caused by repetitive, one-directional teaching. This community service initiative combined Service Learning (SL) and Participatory Action Research (PAR) to introduce basic Arabic instruction alongside a redesigned tahfidz process over a two-week period (21 February–5 March 2026). Twenty-four children took part in the Arabic class and twenty-one in the tahfidz program. Data were gathered through observation, a focus group discussion, and daily evaluation sheets, and were analyzed across two intervention cycles following a plan-act-observe-reflect sequence. In the Arabic class, drill practice, the mubasyarah (direct) method, and communicative techniques paired with visual media such as matching boards and flashcards produced measurable gains in vocabulary recognition and simple conversational exchange. In the tahfidz program, replacing rote repetition with a fun-learning approach and a participatory appreciation system – daily evaluation sheets tied to small rewards – raised both attendance and the completion rate of memorization targets. A parallel online Ta’lim session engaged parents (Ummahat) in supporting home-based learning. The findings suggest that pairing Service Learning’s structured reflection with Participatory Action Research’s cyclical, community-driven problem-solving can resolve demotivation in traditional Qur’anic education while leaving behind a durable foundation for Arabic-language instruction